Green Economy Development Through Educational Tourism in the English Village of Pare, Kediri - Auny Vidiyan Imsawati; Supardal; Adji Suradji Muhammad; Yeyen Subandi4 (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2026)
The English Village in Pare District, Kediri, has contributed to the real economic sector, felt by the community. In fact, the English Village is currently not only in Pelem Village, but has expanded to surrounding villages, including Tulungrejo Village. The English Village has become a lever for the community's economy. The average number of visitors during off-peak hours reaches 5,000 people per day and during school holidays reaches 15,000 people per day. The large number of people visiting the English Village has had a significant economic impact. This study will focus more on how the green economy development model in the development of the English Village as an educational tourism in Pare District, Kediri Regency, East Java. Using qualitative research methods and focus group discussions, the model will be revealed in an effort to grow the green economy through educational tourism. The findings of this study indicate that the Language Village Forum and the Tulungrejo Village Government have not been optimal in developing the green economy through educational tourism.